Mathematics
safreenakbar
46

8y - (2y - 3) = 9 please help!! Explain how you get to the answer

+4
(2) Answers
Charity45

first, remove the parentheses ( 8y-2y-3=9)  then combine like terms (6y-3=9)  next you want to get rid of the three so add it to both sides (6y = 12)  and lastly divide both sides by six (y=2)

JocelynDaubs355

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :  8*y-(2*y-3)-(9)=0  Pull out like factors : 6y - 6  =   6 • (y - 1)    Solve :    6   =  0 y = 1 

Add answer